KEPEMIMPINAN ISLAMI, KEPUASAN KERJA, KOMITMEN KERJA, DAN LOYALITAS KERJA KARYAWAN BANK SYARIAH MANDIRI DI SIDOARJO - Adiba, Elfira Maya (al-Uqud : Journal of Islamic Economics, 2018)
Human resources is the main asset in the company, so the company should pay more attention to this aspect. Islamic leadership is not just a relationship between leaders and subordinates, but more than that, the leader must also be able to give a direct, protect, and treat their employees fairly. It is better known as servant leadership which is a leadership with moral approach based on ethics, morality, and spirituality. This study aims to determine the influence of Islamic leadership, job satisfaction, and job commitment to the job loyalty of the employee of Bank Syariah Mandiri in Sidoarjo. This research used multiple regression. The results of this study are Islamic leadership, job satisfaction, and job commitment simultaneously have a positive and significant impact on job loyalty of employee of Bank Syariah Mandiri in Sidoarjo